Public Private Partnership as a Treatment Strategy for Tuberculosis Under Dots in Coastal South India - S., Rama Prakasha; G., Suresh; D'sa, Ivor Peter; S., Shobha Shetty; S., Ganesh Kumar; Shetty, Manamohan (Journal of Health and Allied Sciences NU, 2012)
Limited information is available regarding the functioning of DOTS (Directly Observed Treatment Short course) center for tuberculosis treatment under public private partnership with a medical college hospital. The present study was done to assess the various parameters related to the effectiveness of follow up treatment and its outcome in a DOTS center attached to a medical college hospital in coastal South India.Reports of patients with tuberculosis diagnosed and treated under Revised National Tuberculosis Control Programme at KS Hegde Medical College hospital DOTS center under Mangalore TB unit were reviewed retrospectively for the period from July 2004 to June 2011. Data was described in proportion and chi square test was applied to assess the association of cases with age group and sex. Among 60 patients serially registered under DOTS, 41 (68.33 %) cases were females and 19 (31.67%) cases were males. Maximum number of cases belonged to 15-29 years age group (20, 33.3%) and the difference observed between the categories of TB and age group was found to be significant (P<0.001). Overall 23 (38.33%), 12 (20%) and 25 (41.67%) cases received Cat-I, Cat-II and Cat-III treatment respectively. Success rate for new smear positive cases was 92.85% (13/14) and for Re-treatment smear positive cases was 88.89% (8/9). Sputum conversion rate among new smear positive cases (n= 14) at 2 months and 3 months was 85.71% and 92.86% respectively. Sputum conversion rate for Re-treatment cases (n=9) at 2 months and 3 months was 55.56% and 88.89% respectively. RNTCP is running successfully in this DOTS center with very low treatment failure rate and better outcome indicators, highlighting the importance of public private partnership of poorly functioning DOTS centers with medical colleges.
Keywords: Public Private Partnership; DOTS strategy; Tuberculosis